Control of blood vessel formation by Notch signaling - Tetzlaff, Fabian; Fischer, Andreas (Molecular Mechanisms of Notch Signaling, 2018)
Blood vessels span throughout the body to nourish tissue cells and to provide gateways for immune surveillance. Endothelial cells that line capillaries have the remarkable capacity to be quiescent for years but to switch rapidly into the activated state once new blood vessels need to be formed. In addition, endothelial cells generate niches for progenitor and tumor cells and provide organ-specific paracrine (angiocrine) factors that control organ development and regeneration, maintenance of homeostasis and tumor progression. Recent data indicate a pivotal role for blood vessels in responding to metabolic changes and that endothelial cell metabolism is a novel regulator of angiogenesis. The Notch pathway is the central signaling mode that cooperates with VEGF, WNT, BMP, TGF-β, angiopoietin signaling and cell metabolism to orchestrate angiogenesis, tip/stalk cell selection and arteriovenous specification. Here, we summarize the current knowledge and implications regarding the complex roles of Notch signaling during physiological and tumor angiogenesis, the dynamic nature of tip/stalk cell selection in the nascent vessel sprout and arteriovenous differentiation. Furthermore, we shed light on recent work on endothelial cell metabolism, perfusion-independent angiocrine functions of endothelial cells in organ-specific vascular beds and how manipulation of Notch signaling may be used to target the tumor vasculature.
Gesehen am 31.07.2019